Encíclica Laudato Si’ : elementos fundamentais para uma ética socioambiental - Furmann, Moisés (2021)
This work seeks to reflect on the socio-environmental ethics instigated by Pope Francis' Encyclical Laudato Si’, which addresses the care of the common home in today's context. The Encyclical questions the way of life of human beings on the planet and contextualizes the situation in which creation finds itself, with harsh criticisms of the economic, political and social system that is leading humanity into a spiral of destruction. The Supreme Pontiff's approach includes scientific data provided by specialists who are dedicated to research on the impacts caused by human action on the planet and integrates the theological vision of tradition with the reflections that are part of the agendas of Episcopal Conferences from different parts of the world. The Catholic Church, especially after Vatican II, has been reflecting on human dignity on the occasion of the signs of the times, in the Church's Social Doctrine. Laudato Si’ is a milestone in the reflection on ecology within the Catholic Church, which is open to dialogue with the world in systemic crisis to build a new model of human life on the face of the earth.